Margarita Moreira: amores, amistades, y los grupos de cripto-judíos portugueses en México, siglo XVII - Robert J. Ferry (Nuevo mundo - Mundos Nuevos, 2006)
Margarita Moreira was a woman who lived on the margins of the world of Mexico’s crypto Jews during the first half of the seventeenth century1.  The essay examines her words, especially the indiscreet comments she made about her love for a man who was a prisoner of the Holy Office.  It is a love story set in the context of the encounter between the Mexican Inquisition, an institution that was then in the process of realizing dramatic changes, and the crypto Jews, who did not, in fact, all respond in the same way to the problem of keeping the secret of their faith.